Rapid Determination of Cypermethrin and Permethrin in Crucian by Matrix Solid-Phase Dispersion Coupled with Gas Chromatography - Qiao, Fengxia; Yan, Hongyuan (Asian Journal of Chemistry, 2012)
A simple pretreatment and analytical method was developed and validated for the quantitative determination of cypermethrin and permethrin in crucian samples. The proposed methodology is based on matrix solid-phase dispersion (MSPD), using neutral alumina oxide as dispersant material and diatomite as clean-up absorbent, eluted by n-hexane-dichloromethane (1:1, v/v) and followed by gas chromatography electron capture detection (GC-ECD) on an DB-5 capillary column. Good linearity was observed in a range of 0.0005-0.50 μg/mL and 0.008-4.00 μg/mL for permethrin and cypermethrin, respectively. The average recovery of cypermethrin and permethrin at three levels of spiked samples were ranged from 72.5 % to 106.6 % with RSD £ 6.7 %. The limits of detection based on signal to noise of 3 were 0.004 mg/kg for permethrin and 0.032 mg/kg for cypermethrin. This proposed MSPD-GC-ECD method was satisfactorily applied to different crucian samples.